2019
DOI: 10.1002/srin.201900151
|View full text |Cite
|
Sign up to set email alerts
|

Castability and Inclusions in a Low Sulfur Ca‐Treated Peritectic Steel for Two Deoxidation Techniques

Abstract: Liquid inclusions are important to avoid nozzle clogging during continuous casting of steel. To minimize clogging tendency at a Brazilian steelworks for a low‐sulphur Ca‐treated peritectic steel, deoxidation technique is changed from only Al addition as deoxidant to Fe–Si ferroalloy followed by Al addition, reducing the amount of Al by 20 wt%. Calcium treatment procedure is not changed. According to steelworks data, clogging occurrences are drastically reduced with this process change. In this context, quenche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Moreover, this sequence presented a TO average of 36.0 ppm per heat (see Table 1) in the tundish. In a recent research [31] made with the same continuous casting reactor used in the present work, the authors found 38.7 ppm per heat, as the TO average in the tundish for an appropriate castability of an Al-killed steel grade.…”
Section: Tundish Samplessupporting
confidence: 54%
“…Moreover, this sequence presented a TO average of 36.0 ppm per heat (see Table 1) in the tundish. In a recent research [31] made with the same continuous casting reactor used in the present work, the authors found 38.7 ppm per heat, as the TO average in the tundish for an appropriate castability of an Al-killed steel grade.…”
Section: Tundish Samplessupporting
confidence: 54%
“…-Large inclusions show a large deposition rate. cleanliness improvement experiment -Lowering the oxidation potential -Reducing REM inclusions before CC -Preventing the reoxidation of steel during CC [110] cleanliness improvement experiment -Optimization of refining slag -Improving the soft stirring operation to reduce the steel-slag desulfurization [111] liquid modification of inclusions experiment -Al 2 O 3 modification by Ca treatment [1] liquid modification of inclusions experiment -Replacement Al deoxidation by Si-Al deoxidation to form liquid inclusions after Ca treatment [112] inclusion modification experiment -Increasing Al/Ti ratio in ULC steels to lower the oxidation of Ti [54] inclusion modification experiment -Controlling the liquid fraction of inclusions larger than 20% [113] fluid flow control simulation -Employing a parabolic curve shaped SEN bottom to guide the liquid steel flow in the SEN [114] fluid flow control and coating material experiment -Application the annular step SEN with carbon free liner combined with a multi layer porous upper nozzle [115] fluid flow control simulation -Controlling the internal flow of nozzles by designed chambers or deflectors to decrease the inclusion deposition [116] surface treatment and fluid flow control experiment and simulation -Anticlogging nozzles by applying selected purified raw materials, type of graphite, surface treatment, and new structure for internal flow control of SEN [70] Base material experiment -Changing alumina-graphite nozzles to alumina, zirconia, and zirconia-graphite nozzles to reduce the refractory-steel interactions [117] Coating material experiment -Application of an Al 2 O 3 plasma coated Al 2 O 3carbon nozzle [118] protective coating material experiment -Employing CaO-ZrO 2 -C nozzles to form liquid phase by the reaction of CaO in the coat with Al 2 O 3 [119] coating treatment experiment -CaTiO 3 coating of alumina-graphite SENs [120] coating experiment -Using yttria-stabilized zirconia (YSZ) [121] treatment containing CaTiO 3 coated nozzles to form liquid phase by the reaction between Al 2 O 3 and CaTiO 3 .…”
Section: Rem Oxide Clustermentioning
confidence: 99%
“…[ 18,19 ] Clogging problems can be prevented by transforming the solid alumina and spinel into liquid inclusions that do not attach themselves to the SEN. An efficient way of achieving this is to use calcium treatment. [ 18,20–25 ] Li et al [ 26–28 ] have shown that a small amount of Ca in Al‐killed Ti‐bearing 11Cr stainless steel effectively modifies Al 2 O 3 –TiO x inclusions into liquid oxide inclusions and reduces the stability of the spinel by modifying the solid alumina into liquid calcium aluminate.…”
Section: Introductionmentioning
confidence: 99%